METHODOLOGY FOR ORGANIZING AND CONDUCTING SPORTS EVENTS - Yakubjonov Ikrom Akramjonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article examines the goals and objectives of physical education, and sports activities in educational institutions.